Anticancer Effects Of Tualang Honey On 7,12-Dimethylbenz(A)Anthracene (DMBA)-Induced Mammary Carcinoma In Rats - Kadir, Erazuliana Abd (2011)
Tualang honey (TH) has been reported to have antiproliferative effect and induces apoptosis in various cancer cell lines. The present study was conducted to evaluate the effects of TH on the initiation and progression of 7,12- dimethylbenz(α)anthracene (DMBA)-induced mammary carcinoma in rats. A preliminary study was conducted to establish the optimum DMBA dose for cancer induction. Single administration of 20 or 25 mg DMBA to 45 to 48 days old female rats with bodyweight of less or more than 120 g respectively was able to induce 50% carcinoma incidence.